Políticas Públicas de inclusão para pessoas com deficiência no ensino superior: avaliação das ações de acessibilidade implementadas no Instituto de Cultura e Arte ( ICA) da Universidade Federal do Ceará (UFC) - Bond, Carlos Ernesto (2024)
The Federal University of Ceará (UFC), as a leading public institution, has sought to promote inclusion through the UFC Accessibility Department, created in 2010. This dissertation study, inserted in the context of the professional master's degree program of POLEDUC at the Federal University of Ceará, is entitled: "Public Policies for Inclusion for People with Disabilities in Higher Education: Evaluation of Accessibility Actions Implemented at the Institute of Culture and Art (ICA) of UFC”. The research analyzes the effectiveness of the initiatives promoted by the UFC Accessibility Department since its creation in 2010, focusing on the inclusion of students with disabilities. The work focuses on the Incluir Program, investigating its influence on the construction of a more accessible academic environment. The specific objectives include characterizing the profile of students with disabilities served by the Department, identifying the contributions of the Department's actions to the inclusion of these students in the ICA, and analyzing the perception of the students themselves regarding the relevance of the services provided. Methodologically, the research adopts a qualitative and exploratory perspective, based on the analysis of official documents, legislation and decrees relevant to the theme of inclusion. A case study at UFC's ICA allows us to understand in depth how the policies of the Incluir Program positively impact the accessibility and inclusion of students with disabilities. The dissertation follows ABNT standards, presenting a fluent and judicious academic language, reflecting the seriousness and importance of the topic addressed.